PENGARUH INTENSITAS SCREEN TIME TERHADAP KECENDERUNGAN OVERTHINKING PADA REMAJA - Ria Safaria Sadif; Unhaluddin T Kurniawan; Hera Asmara (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to examine the effect of screen time intensity on the tendency toward overthinking among adolescents. The research employed a quantitative approach using an ex post facto design. The sample was selected through purposive sampling based on criteria relevant to the research objectives. Data were collected using a screen time intensity scale and the Ruminative Response Scale (RRS-10) to measure the tendency toward overthinking. Data were analyzed using simple linear regression. The findings indicate that screen time intensity has a significant effect on adolescents' tendency to engage in overthinking. Higher durations of digital device use are associated with a greater likelihood of repetitive, excessive, and difficult-to-control thoughts. These findings suggest that digital media use is closely related to adolescents' psychological well-being. Therefore, more responsible and balanced screen time management is essential to maintain mental health and support optimal psychological development among adolescents.